ESTUDO COMPARATIVO DA EVAPOTRANSPIRAÇÃO DE REFERÊNCIA ENTRE LOCALIDADES NO ESTADO DE SÃO PAULO E NA PROVÍNCIA DE HABANA - Sousa Pereira, Francisca Franciana; Dal Pai, Enzo; Vázquez Montenegro, Ranses J.; Sánchez Román, Rodrigo Máximo; Orellana González, Alba Maria Guadalupe; Escobedo, João Francisco (IRRIGA, 2018)
ESTUDO COMPARATIVO DA EVAPOTRANSPIRAÇÃO DE REFERÊNCIA ENTRE LOCALIDADES NO ESTADO DE SÃO PAULO E NA PROVÍNCIA DE HABANA FRANCISCA FRANCIANA SOUSA PEREIRA1; ENZO DAL PAI2; RANSES J. VÁZQUEZ MONTENEGRO3; RODRIGO MÁXIMO SÁNCHEZ ROMÁN4; ALBA MARÍA GUADALUPE ORELLANA GONZÁLEZ5 E JOÃO FRANCISCO ESCOBEDO6 1Professora Depto. de Engenharia Rural - UNESP/FCA, C.P. 237; CEP: 18610-307 – Botucatu, SP – Brasil. E-mail autor principal: francanasousap@gmail.com 2Professor Depto. de Engenharia Rural - UNESP/FCA, Botucatu, SP – Brasil. 3Geográfo, Especialista em Meteorología agrícola do Centro de Meteorología Agrícola, Instituto de Meteorología La Habana, Cuba. 4Professor Depto. de Engenharia Rural - UNESP/FCA, Botucatu, SP – Brasil. 5Pós- Doutora Depto. de Engenharia Rural - UNESP/FCA, Botucatu, SP - Brasil. 6Professor Depto. de Engenharia Rural - UNESP/FCA, Botucatu, SP – Brasil. 1 RESUMO A FAO propôs a evapotranspiração de referência (ETo) a fim de comparar a evapotranspiração em diferentes regiões, isso porque a maioria das equações empregadas na estimativa da evapotranspiração são empíricas e limitadas a serem usadas para locais e climas similares àqueles em que as mesmas foram determinadas. O objetivo deste estudo foi analisar a diferença nos valores calculados de ETo para Botucatu e Piracicaba (Brasil) e Güira de Melena (Cuba), em uma base de dados de 30 anos, trabalhada na partição diária. Avaliaram-se diferenças sazonais entre os anos e entre as localidades e posteriormente a influência dos climas locais nestas diferenças dos valores de ETo. Os elementos climáticos temperatura máxima e mínima do ar, umidade relativa do ar, velocidade do vento a 2 m de altura e insolação foram obtidos das estações meteorológicas convencionais. Os valores da evapotranspiração em Cuba foram maiores durante os meses de verão no Hemisfério Norte. Os maiores valores de evapotranspiração em Botucatu e Piracicaba ocorreram nos meses de verão no hemisfério Sul. Existe correlação entre as três localidades mesmo com a distância entre as mesmas. Palavras-chave: demanda hídrica, irrigação, recursos hídricos, Penman-Monteith SOUSA PEREIRA F. F.; DAL PAI, E.; VÁZQUEZ MONTENEGRO, R. J.; SÁNCHEZ ROMÁN, R. M.; ORELLANA GONZÁLEZ, A. M. G.; ESCOBEDO, J. F. COMPARATIVE STUDY OF REFERENCE EVAPOTRANSPIRATION BETWEEN LOCALITIES IN SÃO PAULO STATE AND IN THE HABANA PROVINCE 2 ABSTRACT FAO proposed the reference evapotranspiration to compare evapotranspiration in different areas, because most equations employed in estimating evapotranspiration are empirical and limited to be used for in local and climates similar to those in which they were determined. The objective of this study was to analyze the difference in the calculated values of ETo for Botucatu and Piracicaba (Brazil) and Güira Melena (Cuba), on a basis ofbased on 30- years of data. Were evaluated sSeasonal differences between years and between locations were assessed and subsequently the influence of local climates on these ETo values differences in the values of ETo. The cClimatic elements maximum (Tmax) and minimum temperature (Tmax) and minimum (Tmin), relative humidity (RH), wind speed at 2 m height (U2) and solar radiation (n) were obtained from conventional meteorological stations. The values of eEvapotranspiration values in Cuba were higher during the summer months in the Northern Hemisphere. The highest values of evapotranspiration values in Botucatu and Piracicaba occurred in the summer months in the Southern Hemisphere. Correlation exists between the three locations with the same distance between them. It was concluded from the methodology used that the three localities have different values of evapotranspiration values and despite being in different hemispheres the evapotranspiration among Piracicaba and Güira Melena are closer than the one verified between Botucatu and Piracicaba. Keywords: water requirement, evapotranspiration, irrigation, water resources, Penman Monteith